Vehicle-to-Everything Communication - Spitalova, Zuzana (Communications - Scientific Letters of the University of Zilina, 2023)
With an increasing number of vehicles, there is a need for reliable and secure communication between subjects participating in the dynamic traffic environment. This kind of communication is called V2X (Vehicle-to-Everything). It can also contribute to higher level of autonomous driving. The V2X model operation is enabled by use of the newest technologies and standards, defined by 3GPP Organization. In this paper, a review of the V2X communication models, available technologies and standards are studied.
Keywords: VANET; DSRC-V2X; C-V2X; 5G NR; IEEE 802.11bd